Corporate governance and valuation of government linked companies in Singapore. - Ong, Chin Guan. (2008)
We investigate corporate governance under an alternative ownership/control structure, the government linked companies (GLCs) in Singapore. We show that GLCs have better corporate governance than a control group of non-government owned companies. Finally, we find evidence that investors in the Singapore stock market value good governance.